Novel bHLH and WD40 transcription factors from turmeric (Curcuma longa L.) as putative regulators of curcumin biosynthesis - Mol, P. Prashina; Aparna, R.S.; Sheeja, T.E.; Deepa, K. (Journal of Plantation Crops, 2021)
Turmeric, the golden spice belonging to the family Zingiberaceae, is enriched with biologically active curcuminoids composed of curcumin, demethoxycurcumin and bisdemethoxycurcumin. Curcuminoids are phenylpropanoid derivatives, and the biosynthetic pathway is controlled by several transcription factors (TFs). bHLH, WD40 and MYB TFs are the most important TFs regulating phenylpropanoid biosynthesis in plants. Through comparative transcriptome analysis of high and low curcumin germplasm accessions, 20 TFs belonging to the classes bHLH, WD 40, NAC, WRKY and bZIP, which showed differential expression with respect to curcumin, were identified. Among these, two bHLH and one WD40 TFs showed maximum comparative fold change and negative correlation vis-a-vis curcumin content in quantitative real-time polymerase chain reaction (qRT-PCR) analysis. The results of comparative transcriptome and qRT-PCR analyses were in congruence, indicating their putative role as negative regulators.